SECONDO: A Platform for Cybersecurity Investments and Cyber Insurance Decisions - Farao, Aristeidis; Panda, Sakshyam; Menesidou, Sofia Anna; Veliou, Entso; Episkopos, Nikolaos; Kalatzantonakis, George; Mohammadi, Farnaz; Georgopoulos, Nikolaos; Sirivianos, Michael; Salamanos, Nikos; Loizou, Spyros; Pingos, Michalis; et al. (My University, 2020)
This paper represents the SECONDO framework to assist organizations with decisions related to cybersecurity investments and cyber-insurance. The platform supports cybersecurity and cyber-insurance decisions by implementing and integrating a number of software components. SECONDO operates in three distinct phases: (i) cyber-physical risk assessment and continuous monitoring; (ii) investment-driven optimized cyber-physical risk control; and (iii) blockchain-enabled cyber-insurance contract preparation and maintenance. Insurers can leverage SECONDO functionalities to actively participate in the management of cyber-physical risks of a shipping company to reduce their insured risk.
Keywords: Cyber Physical System; Insurance; Investments; Security of data; Cyber physicals; Cyber security; Shipping companies; Software component